Microecological insight to fungal structure and key fungal communities regulating nitrogen transformation based on spatial heterogeneity during cow manure composting by multi-angle and multi-aspect analyses. (1st April 2022) - Sun, Yu; Liu, Xinda; Sun, Lei; Men, Mengqi; Wang, Bo; Deng, Liting; Zhao, Liyan; Han, Yue; Jong, Chol; Bi, Ruixin; Zhao, Mingming; Li, Xiang; et al.
Graphical abstract: Highlights: Spatial heterogeneity is a unique feature of composting. Unclassified Ascomycota genus was the biomarker in all layers of compost. Different fungal communities drove synergistically nitrogen transformation. Multi-aspect analysis was helpful to identify key fungi affecting N transformation. Zopfiella and Preussia determined NO3 − -N transformation in top and middle layers. Abstract: Composting is the mainstream technology for the treatment of agricultural solid waste, but limited efforts were made to investigate fungal composition and its contributions to nitrogen transformation in different depths of compost. In this study, spatial distributions of fungi were analyzed using high throughput sequencing by multi-angle analyses, and the key fungal communities determining nitrogen transformation were quantified and identified by multi-aspect analyses during cow manure composting. Multi-angle analyses showed that fungal structure, biomarkers and trophic mode composition varied in different layers, revealing that spatial heterogeneity is the distinctive attribute of composting system. Ascomycota and Basidiomycota were dominant phyla during composting, the two phyla peaked in top and bottom layer respectively. At mesophilic stage, Tremellales, and unclassified Ascomycota (order) were biomarkers in top and middle layer respectively, and so were Remersonia, Pyrenochaetopsis, and Wallemia in bottom layer by LEfSe analysis. Based on multi-aspect analyses, Unclassified Dothideomycetes mainly affected NH4 + -N transformation both in top (1.2816***) and middle layers (1.1726*) . Trichocladium asperum (0.9536***) and Zopfiella (−0.9484***) mainly affected TN transformation in top layer. Guehomyces pullulans (−0.9684**) and Preussia (−1.0508**) regulated NO3 − -N transformation in middle layer. Thermomyces lanuginosus (0.7127***) and Typhula sp. UW973129 (0.7298***) were the key species promoting TN and C/N transformation in bottom layer, respectively. Interestingly, different fungal communities showed a complex network interaction driving nitrogen transformation, and the abundance of microbial community could be conducive to characterizing nitrogen transformation in the vertical space of composting.